Optimization of Carboxymethylcellulose (CMC) for Environmentally Friendly TNI Rations Packaging Formulation Based on Polysaccharides - Rhomadon, Fajar Ismail; Hasibuan, Anggi Khairina Hanum; Kurniadi, Tedi; Ramadhanty, Chrisna Prawiradhiva; Azzida, Putry Wanda (MUNISI: Military Mathematics and Natural Sciences, 2025)
Conventional plastic waste is difficult to decompose and has the potential to leave traces in the TNI field of operations. This condition has encouraged the development of polysaccharide-based bioplastics as a safe, environmentally friendly, and easily degradable alternative for ration packaging. This study aims to optimize the concentration of carboxymethylcellulose (CMC) as a filler in the formulation of polysaccharide bioplastics for TNI ration packaging. The method used was a literature review on the effect of CMC addition on the physical and mechanical properties of bioplastic films. The results of the study showed that the addition of CMC generally increased tensile strength and water absorption, but also accelerated dissolution and the rate of biodegradation. The optimum concentration varied depending on the type of polymer used. Therefore, the selection of CMC concentration must be adjusted to the application objective, whether to increase mechanical strength or accelerate biodegradation, and needs to be validated through mechanical and degradation tests under real conditions. Compliance with bioplastic quality standards and the use of safe additives are highly recommended for application in TNI ration packaging.